Indigenous child’s right to access justice in Peru - Avellaneda Vásquez, Jainor (2024)
This article aims to analyse how the Peruvian legal system, in harmony with international human rights systems, protects the indigenous child’s right to access justice. The methodology applied is qualitative, documentary in nature. The results highlight the importance of promoting access to justice for indigenous children based on the special valuation of the principles of human dignity, equality and non-discrimination, and the best interests of the child, seeking to reverse any situation of vulnerability with differentiated treatment in the courts. At the beginning, the right of access to justice for indigenous children is addressed on the basis of international human rights instruments, followed by a review of the normative and jurisprudential mechanisms and public policy initiatives that the local legal system has in place to protect this right.